(untitled) (Global Journals of Research in Engineering, 2024)
The consumption of fruits and vegetables is known to confer numerous health benefits to individuals owing to their remarkable nutrient density as agricultural produce Rapid decay of perishable items leads to a reduction in quality and nutrient content Additionally these items are highly susceptible to spoilage The implementation of cold chain technologies has resulted in a reduction of quality loss experienced by fruits and vegetables during their transportation from the farm to the consumer Despite efforts to minimize waste a considerable proportion 50 of fresh agricultural products is still lost during the processes of packaging pre-cooling transportation and storage The quality loss experienced by perishable foods like fruits and vegetables during packaging storage and transit along the cold chain is the primary focus of this article Existing research points to digital twins and the Internet of Things IoT as two possible technological intervention paths for linked supply chains Using a digital twin or a virtual clone of a farm has the potential to increase productivity and efficiency while decreasing resource use The provision of approximative assessments of food temperatures after harvest is one example of how the Internet of Things IoT could help with quality monitoring and management The aforementioned advancements will facilitate the detection and mitigation of supply chain challenges that have the potential to undermine the freshness and quality of perishable goods The objective of this research is to present a conceptual model for the integration of supply chain in urban food systems with a specific focus on digital technology interventions Furthermore this study aims to provide insights into the potential areas of investigation for future research on the digitization of the food supply chain